2014
DOI: 10.1371/journal.pone.0108446
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Determinant of α4β7 Binding in the V2 Loop of HIV-1 gp120

Abstract: The peptide segment of the second variable loop of HIV-1 spanning positions 166–181 harbors two functionally important sites. The first, spanning positions 179–181, engages the human α4β7 integrin receptor which is involved in T-cell gut-homing and may play a role in human immunodeficiency virus (HIV)-host cell interactions. The second, at positions 166–178, is a major target of anti-V2 antibodies elicited by the ALVAC/AIDSVAX vaccine used in the RV144 clinical trial. Notably, these two sites are directly adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 20 publications
3
44
1
Order By: Relevance
“…In support of this hypothesis, mouse anti-V2 MAbs have been shown to inhibit binding of biotinylated gp120 MN to the ␣4␤7 ϩ ␤1 Ϫ RPMI-8866 B lymphoma cell line (14). Two human anti-V2 MAbs from our laboratory, 697 and 2158, also inhibited binding of gp120 MN to CD4 ϩ cells and activated CD8 ϩ cells (17). The extent to which such blocking by V2-specific Abs occurs in vivo is not known; however, it has been reported that the envelopes of most HIV strains do not bind to ␣4␤7 (18), a result that may be dependent upon the nature of the carbohydrate residues on the Env protein.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…In support of this hypothesis, mouse anti-V2 MAbs have been shown to inhibit binding of biotinylated gp120 MN to the ␣4␤7 ϩ ␤1 Ϫ RPMI-8866 B lymphoma cell line (14). Two human anti-V2 MAbs from our laboratory, 697 and 2158, also inhibited binding of gp120 MN to CD4 ϩ cells and activated CD8 ϩ cells (17). The extent to which such blocking by V2-specific Abs occurs in vivo is not known; however, it has been reported that the envelopes of most HIV strains do not bind to ␣4␤7 (18), a result that may be dependent upon the nature of the carbohydrate residues on the Env protein.…”
mentioning
confidence: 66%
“…Indeed, the protective role of anti-V2 Abs against HIV-1 infection may eventually prove to be polyfunctional. It may include other functions not explored here, such as additional Fc receptor-related activities and/or the inhibition of the gp120/ ␣4␤7 interaction which has been shown previously despite some remaining controversy (14,17,18).…”
Section: Discussionmentioning
confidence: 96%
“…ab initio folding was performed using ICM-Pro software (Molsoft LLC, La Jolla, CA, USA) as previously described [9, 15, 16]. Briefly, the 3D atomic structure corresponding to each peptide sequence was built.…”
Section: Methodsmentioning
confidence: 99%
“…The two others were secondary study variables: a gp120 peptide microarray and an ELISA using a non-biotinylated peptide equivalent to the V2 segment from positions 161 to 183 (numbering based on the Hxbc2 reference strain of HIV) of the MN strain of HIV (MN peptide) as the detection reagent [6]. Neither of these two latter probes were glycosylated entities, so they contained only natural amino acids, and they overlapped at the V2 peptide segment from positions 165 to 181[8, 9]. Two independent sieve analysis of RV144 data identified position 169 within this segment as correlating with vaccine efficacy, one of which identified a specific HLA allele/cytotoxic T-cell epitope (CTL) in the MN peptide [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the contribution of anti-V3 Abs in reducing infection may depend on their potential to neutralize HIV-1 while the role of anti-V2 Abs may depend on other functions, including the interference of virus that binds to T cells that express integrin α4β7, as some studies suggest (12, 13). Although anti-V3 mAbs neutralize mainly tier 1 pseudoviruses, most anti-V3 mAbs can neutralize one to several tier-2 and -3 viruses (11, 14).…”
Section: Introductionmentioning
confidence: 99%